Top stories of 2008. Antiretroviral rollout--successes and challenges. - Friedland, Gerald H (AIDS clinical care, 2009)
The continued success of ART rollout programs will depend on efforts to prevent resistance and ensure adequate follow-up.
Keywords: Anti-HIV Agents; CD4 Lymphocyte Count; Child; HIV Infections; Humans; Reverse Transcriptase Inhibitors; Viral Load